Analisis Habituasi Profil Pelajar Pancasila Pada Sekolah Penggerak Kota Ambon - Musidi, Darsiansi; Lisye Salamor; Ritiauw, Samuel Patra (Jurnal Pendidikan Kewarganegaraan Undiksha, 2025)
This study aims to determine the profile habituation of Pancasila students at driving schools in Ambon City, using a survey research method with a quantitative descriptive approach. The population consisted of grade 5 students at two driving schools (SDN 64 Ambon and SDN 70 Ambon) as well as the principal and class teacher as informants. Using interview instruments, questionnaires, and learning achievement tests, data analysis techniques in this study used Likert scale measurements with a range of rating scales, namely: Strongly Disagree: 1, Disagree: 2, Undecided: 3, Agree: 4, and Strongly Agree: 5. The results of the research show that the habituation of Pancasila student profiles is created in the learning process at the Ambon City Pengmobil Elementary School because it is supported by the quality of educators, school efforts (vision, mission, facilities and infrastructure and discipline) of the school used as a research site. The conclusion of this study is that according to the results of the analysis conducted by the author that from data processing on the Habituation profile of Pancasila students in the form of a questionnaire (questionnaire) with 79% being approved at SD Negeri 64 Ambon and 82% being approved at SD Negeri 70 Ambon: